Circulating cytokines associated with clinical outcomes in advanced non‐small cell lung cancer patients who received chemoimmunotherapy. Issue 2 (25th November 2021) - Shi, Yuequan; Liu, Xiaoyan; Du, Juan; Zhang, Dongming; Liu, Jia; Chen, Minjiang; Zhao, Jing; Zhong, Wei; Xu, Yan; Wang, Mengzhao
Abstract: Background: Pretreatment and on‐treatment plasma cytokine levels in predicting clinical benefit in patients with advanced non‐small cell lung cancer (NSCLC) treated with anti‐programmed death‐1 (PD‐1)‐based chemotherapy is still a matter of debate. Methods: We measured 12 kind of plasma cytokines in patients with stage III/IV NSCLC before and during treatment with anti‐PD‐1 based chemotherapy. Associations with best overall response, and survival including progression‐free survival (PFS) and overall survival (OS) were assessed using Chi‐square test and Kaplan–Meier plots with log‐rank test, respectively. Logistic regression and Cox regression were used to determine independent risk factors. Results: Of a total of 60 patients, high‐level of pretreatment interleukin‐2 was associated with longer PFS (log rank p  = 0.049), while high‐level of pretreatment interleukin‐8 was associated with shorter OS (log rank p  = 0.006). Increased on‐treatment interleukin‐1β (IL‐1β) was associated with both better response (odds ratio [OR] 6.233, 95% confidential interval [CI]: 1.451–26.344, p  = 0.013) and longer PFS (hazard ratio [HR] 0.305, 95% CI: 0.127–0.730, p  = 0.008). On the contrary, increased on‐treatment interleukin‐6 (IL‐6) was associated with a worse response (OR 0.015, 95% CI: 0.001–0.400, p  = 0.012), worse PFS (HR 2.639, 95% CI: 1.163–5.991, p  = 0.020) and worse OS (HR 2.742, 95% CI: 1.063–7.074, p  = 0.037). Increased interferon‐γ (IFN‐γ) was found to be associated with better PFS (HR 0.336, 95% CI: 0.153–0.745, p  = 0.007). Conclusions: In patients with advanced NSCLC who received chemoimmunotherapy, on‐treatment increased IL‐1β and IFN‐γ may serve as positive indicator of efficacy, while on‐treatment increased IL‐6 might play a predictive role of worse clinical outcome. Abstract : We retrospectively measured 12 kind of plasma cytokines in patients with stage III/IV non‐small cell lung cancer before and during immune checkpoint inhibitor (ICI)‐based chemoimmunotherapy. Results showed that increased on‐treatment interleukin‐1β, interferon‐γ were related to longer progression‐free survival (PFS). Increased on‐treatment IL‐6 was related to shorter PFS. We suggest the indicative role played by circulating cytokines and efficacy of ICI‐based chemotherapy.